An exploration of values among consumers seeking treatment for borderline personality disorder - Simone R. Mohi; Frank P. Deane; Anne Bailey; Dianne Mooney-Reh; Danielle Ciaglia (Borderline Personality Disorder and Emotion Dysregulation, 2018)
Abstract Background Consumer feedback identifies a new challenge in the treatment of borderline personality disorder (BPD) is to address the discrepancy between clinical treatment targets and the more personally meaningful goals people are seeking in treatment. This highlights the need to increase clarification of people’s values and link these to therapy goals. The current study explores ways in which individuals with BPD identify with values across key life domains. Methods At initial assessment 106 consumer participants attending an outpatient clinic for the treatment of BPD completed the Personal Values Questionnaire by Blackledge and colleagues. This 90-item measure asks participants to respond to different value appraisals such as importance, commitment, desire to improve, success and, motivation across nine life domains. These included: relationships, health & wellbeing, education & personal development, work & career, spirituality, recreation & leisure, and community involvement. Results A consistent pattern of value appraisals was found across all life domains. Specifically, life domains were endorsed as highly important but participants reported significantly lower levels of value commitment, desire to improve and success. Successful value pursuit also related differentially to value motivations (internal vs. external) depending on the particular life domain. Relationships with family, friends and romantic partners, as well as health & wellbeing were most important compared to other life domains. Conclusions The findings suggest that people with BPD identify with values and prioritise different life domains in terms of importance. Our results show discrepancies between higher importance and lower commitment, desire to improve and success at living in line with what is valued. Identification of such discrepancies provides opportunities to more effectively support consumers with BPD to prioritise goals that are consistent with valued domains. These findings offer new insights for cultivating the personal meaning consumers are currently seeking in BPD treatments.